EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DALAM MEMENUHI KETERCAPAIAN KURIKULUM MASA PANDEMI COVID 19 DI SDN PULOJAYA 1 KECAMATAN LEMAHABANG KABUPATEN KARAWANG - Yasin MN; Ibnu Muthi; Asep Dudin Abdul Latip (JURNAL ILMIAH EDUKATIF, 2021)
The research focused on the effectiveness of PAI learning and character in fulfilling the Covid 19 curriculum at SDN Pulojaya 1, Lemahabang District, Karawang Regency, West Java. The purpose of the research is to find out the Islamic Religious Education Curriculum and Character Education during the COVID-19 emergency, namely a curriculum that adapts to the emergency curriculum, compiled as a guideline for organizing learning activities during a pandemic emergency to achieve educational goals taking into account the existing situation and conditions Supporting factors and Inhibiting factors. The method used is the research method used is descriptive with a qualitative approach. through The research method used is descriptive with a qualitative approach. through interviews, observations and documentation studies. Data comes from interview scripts, field notes, photos, videos, tapes, personal documents, notes or memos, and other official documents through primary and secondary data. The results of the study of Islamic Religious Education Learning and Budi Pekerti in fulfilling the achievement of the Covid-19 pandemic emergency curriculum were quite effective, it was seen in the learning activities that still referred to the signs The existing curriculum is related to: Consistency of Learning Planning design and its implementation, Number of hours in one hour lesson, Achievement of the material delivered, Learning procedures during the covid 19 period, Providing motivation for apperception activities, Final activities on online learning.